Decompression as an effective primary approach to large radicular cyst in maxillary sinus: A case report - Biočanin Vladimir; Brajković Denis; Stevanović Momir; Tatić Zoran; Andrić Miroslav; Brković Božidar (Vojnosanitetski Pregled)
Introduction. Therapeutic approach to jaw cysts may depend on their dimensions and localization. Enucleation of cystic lesion is not always preferable in the first act, especially if large cysts are in close proximity to important anatomical structures. The aim of this paper was to present the outcome of the treatment protocol comprising preoperative decompression and subsequent enucleation of a large maxillary cyst. Case report. A 21-year-old male patient with large asymptomatic radicular cyst in the right maxillary sinus was presented to our clinic. Cone-beam computed tomography (CBCT) showed a large cyst, which perforated the right anterior maxillary wall by 1.5 cm, and was in the intimate contact with the orbital floor. Surgical treatment of the cystic lesion comprised: preoperative decompression with biopsy in the first act and enucleation, performed under general anesthesia, 6 months after the observation period. Conclusion. Decompression with subsequent enucleation proved to be effective treatment of large radicular cyst in maxillary sinus with low-morbidity. [Projekat Ministarstva nauke Republike Srbije, br. 175021]